Intracranial Hemorrhage Following Oral Low-Dose Methotrexate After Multiple Toxicities Caused by High-Dose Methotrexate in Childhood Acute Lymphoblastic Leukemia - Ning Xin; Zhou Fen; Cheng Li; Xiao Yan; Jin Runming (Frontiers Media S.A., 2019)
An 11-year-old male patient with the deletion of IKZF1 (Ikaros family zinc finger 1) and positive Breakpoint Cluster Region-C-Abelson oncogene 1(BCR-ABL1) acute lymphoblastic leukemia developed mucositis, gastrointestinal toxicity, hepatotoxicity, myelosuppression, and severe dermatologic toxicity during the first and second courses of high-dose methotrexate. The patient recovered completely after therapy. However, intracranial hemorrhage (ICH) occurred following oral methotrexate at a dose of 25 mg/m2 in maintenance treatment, and he had neurological sequelae including hemiplegic paralysis.